PELATIHAN OPTIMASI MESIN PENCARI (SEO) PADA KONTEN WEB PKBM TUNAS MELATI PELAIHARI - Agustian Noor; Ahmad Rusadi Arrahimi; Billy Sabella; Eka Wahyu Sholeha (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
This service utilizes the steps of the Search Engine Optimizer (SEO) in maximizing the search for website addresses to accelerate recognition and marketing. The output target is the optimization of the Tunas Bangsa website through SEO which includes the ease of finding website addresses for visitors on search engines. The use of automated search engines can lower promotional costs than using traditional and conventional media such as newspapers, radio broadcasts, television, and so on. Website addresses that are used as promotional tools and digital introductions by the Tunas Melati Community Learning Activity Center must be designed properly and correctly, so that they can be an appropriate and optimal promotional tool. This step is followed by website optimization so that it is detected and indexed at the top on search engines like Google. The method used is in the form of steps and the use of SEO plugins on a wordpress-based website. The result of this activity is an optimal website indexing by search engines.